Penile Replantation, Science or Myth? A Systematic Review - Babaei, Ali Reza; Safarinejad, Mohammad Reza (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: Penile amputation is a rare urologic condition for which immediate surgical replantation is warranted. The surgical technique used for repair has been modified and refined. Our aim was to assess the effects of several interventions and management for amputated penis after replantation. Materials and Methods: We searched the MEDLINE (January 1966 to May 2007), EMBASE (January 1988 to January 2007), CINAHL (January 1982 to January 2007), PsycLIT (January 1984 to January 2007), ERIC (January 1984 to January 2007), and the bibliographic data of relevant articles; hand-searched conference proceedings; and contacted investigators to locate studies. All reported cases of penile replantation were studied. We assessed all titles, abstracts, and extracted data from the articles identified for inclusion. Outcome measures included cosmetic outcomes, acceptability, operative time, restoration of erectile function, sensibility of the glans, and long-term outcomes. Results: Eighty patients had undergone penile replantation. There was considerable variation in the interventions, patients, and outcome measures. The majority of the reported cases in this area continue to be of moderate quality, although more recent cases have been of higher quality in terms of both patients' demographics and surgical techniques. Data were not available in all of the cases for many of the outcomes expected to be reported. There were several important variations in the cases studied. Conclusion: The value of the various microsurgical techniques for replantation of the penis remains uncertain. Meticulous microsurgical techniques by experienced surgeons can reduce skin, urethra, and graft loss complications and produce a functional organ; nonetheless, such complications are still highly prevalent.